Upaya Penanganan Pasca Longsor Lintas Purwokerto – Kutoarjo (Studi Kasus Km 423+100 Stasiun Ijo-Tambak) - Pandiangan, Adrian M.T.; Hosang, J.R.C; Septanto, Djoko (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2019)
The safety of train travel is one of the important components in rail freight transport. Reliability of infrastructure is one of the points to support the safety of the railway. Purwokerto cross - a cross Kutoarjo contoured varied geography in which the right - left rail path there are hills and slopes so that this region including areas prone to landslides. As happened in the field there are avalanches in km 423+100 cause interference a train journey. To examine the handling of landslides that have been carried out by PT.KAI used analysis to solve the problem which is done by comparing the handling procedures for handling should be done, in accordance with the existing provisions. The results of the analysis suggest that there are several factors that resulted in the occurrence of such landslides, such as steep slopes, high rainfall intensity at the time and lack of additional protection in the form of plants that can reduce erosion. Therefore the need for further treatment